PENEGAKAN HUKUM TERHADAP PELANGGARAN LALU LINTAS BERUPA PENGGUNAAN KNALPOT RACING DI WILAYAH HUKUMKEPOLISIAN RESOR KOTA PEKANBARU - Tri Zulkhaidir; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
According to the Law of the Republic of Indonesia Number 22 Year 2009 concerning Traffic and Road Transportation Article 285 (1) reads Every person who rides a motorcycle on a road that does not meet the technical requirements and is road worthy includes the exhaust as referred to in Article 106 paragraph (3) juncto Article 48 paragraph (2) and paragraph (3) shall be sentenced to a maximum imprisonment of 1 (one) month or a maximum fine of Rp.250,000.00 (two hundred and fifty thousand rupiah) "but in the implementation there are still many vehicles that use racing exhaust escaped police surveillance. The formulation of the problem in this study is about how law enforcement against perpetrators of racing exhaust violations in the Pekanbaru City Police jurisdiction, What are the obstacles to law enforcement against traffic violations in the form of the use of racing exhausts in the Pekanbaru City Police Department jurisdiction, and how law enforcement efforts against violations traffic in the form of the use of racing exhausts in the jurisdiction of the Pekanbaru City Police Department. The purpose of this study is to find out how law enforcement, obstacles, and how efforts in applying to traffic violations related to law enforcement against traffic violations in the form of the use of racing exhausts in the Pekanbaru City Police jurisdiction. This research is classified as a type of juridical empirical research or sociological legal research. The nature of this research is descriptive research, namely methods intended for exploration and clarification of a phenomenon or reality, describing the problem and the unit under study. Law enforcement against perpetrators of racing exhaust violations in the jurisdiction of the Pekanbaru City Police, there are two attempts to overcome obstacles to law enforcement against perpetrators of racing exhaust violations in the jurisdiction of the Pekanbaru City Police, namely preventive and repressive measures. Keywords: Law Enforcement, Traffic Crimes, Traffic Violations, Racing xhaus